FEATURES OF THE DEVELOPMENT OF CREATIVE ABILITIES IN CHILDREN AGED 5-6 YEARS - Kholmatova Gululya Obidovna (Journals Park Publishing, 2024)
The article highlights the features of the factors influencing the development of creative abilities in children aged 5-6 years, as well as the rules, methods and techniques of the educational process and the forms of its organization.
Keywords: Creativity, educational process, creative activity, creativity, self-discipline, moral qualities of purpose.